APPLICATION OF PEDAGOGICAL PRINCIPLES IN THE DESIGN OF ACADEMIC INFORMATION WEBSITE FKIP UNTAN - Firmansyah, Andang; Yansa, Hemri; Saptahadi, Dwija (Universitas Tanjungpura, 2025)
The purpose of this study is to assess and apply pedagogical principles in the development of academic websites at Universitas Tanjungpura's Fakultas Keguruan dan Ilmu Pendidikan (FKIP). The primary focus of this study is the application of the